The Amentoflavone-Rich Extract of Ouratea fieldingiana Leaves Presents Antioxidant and Anti-inflammatory Activity in Mice - , Lucas Soares Frota, Francisco Glerison da Silva Nascimento, Leonardo Soares Freitas, Francisco Flavio da Silva Lopes, Ramon Róseo Paula Pessoa Bezerra de Menezes, Alana de Freitas Pires, Rondinelle Ribeiro Castro, Ana Maria Sampaio Assreuy, Selene Maia de Morais (Archives of Current Research International, 2024)
Aims: To evaluate the antioxidant and anti-inflammatory effects of the Ouratea fieldingiana leaf extract (OFE) and its main constituent amentoflavone (AMT). Study Design: The phenolic compounds of Ouratea fieldingiana leaves (OFE) were quantified, the chemical structure characterized and the anti-inflammatory effect of OFE and amentoflavone was evaluated in mice paw edema and peritonitis. Place and Duration of Study: The work involved the partnership of the Natural Products Chemistry Laboratory and Inflammation Physio pharmacology Laboratory, between July 2020 and June 2021. Methodology: The OFE was obtained from 70% ethanol extract of O. fieldingiana. OFE was subjected to classic chromatographic column furnishing AMT. The phenolic compounds were characterized by HPLC and quantified by Follin-Ciocalteu methodology. The antiradical potential was evaluated by DPPH and ABTS methods. Anti-inflammatory activity was determined in female Swiss mice received per oral OFE (0.1-10 mg/kg) or sterile saline 60 min before stimulation with carrageenan (300 mg) for quantification of the parameters: edema, abdominal hypernociception, neutrophil migration and oxidative stress markers (reduced glutathione, malondialdehyde, myeloperoxidase and catalase activities). Results: AMT was identified as the main compound in the OFE (292.64 ± 3.87 mg/g extract). OFE has an average inhibitory concentration of 9.81 ± 0.17 µg/mL extract to inhibit the DPPH radical. OFE and AMT inhibited paw edema [OFE: 32% (0-2 h), 28% (2-4 h); AMT: 55% (0-2h); 51% (2-4 h)], neutrophil migration (OFE: 65%; AMT: 67%); myeloperoxidase activity (OFE: 37%; AMT: 45%) and abdominal hypernociception (OFE: 31%; AMT: 35%). OFE, but not AMT, increased catalase activity (57%) and reduced glutathione (62%), but decreased malondialdehyde (69%). Conclusion: The amentoflavone-rich extract from O. fieldingiana leaves presents antioxidant activity in vitro and in vivo, and anti-inflammatory activity in vivo, corroborating the popular use of the plant.